Governance of village development planning deliberations (Musrenbangdes) in Sungai Rambutan City - Khairunnas Khairunnas; Rahmat Rafinzar; Retno Susilowati (Universitas Merdeka Malang, 2023)
This research is motivated by the heterogeneous demographic conditions of Sungai Rambutan Village and is an Independent Integrated City area and as a development and research center village in Ogan Ilir. In particular, this study aims to analyze the implementation of the Musrenbangdes in the perspective of good governance and to describe the collaborative action model that can be applied in the implementation of the Musrenbangdes. The method used in this research is a qualitative research method with a descriptive approach. Data collection was carried out by in-depth interviews with key informants, observations, and literature reviews. Furthermore, the data obtained from the interviews were processed using the NVIVO 12 Plus Software. The results of this study indicate that the implementation of Musrenbangdes in Sungai Rambutan Village has not been maximized. The lack of socialization and knowledge related to the musrenbangdes has an impact on the low participation of the community and the absence of absorption of aspirations in the form of multilevel deliberation from the hamlet level. In addition, the implementation of the musrenbangdes in Sungai Rambutan Village is also constrained by budget availability in accommodating the majority of physical development proposals that require a large budget. Through this research, the researcher provides recommendations for collaborative action models in the implementation of musrenbangdes involving academics and the private sector as a form of problem solving.